2013
DOI: 10.1007/s12263-013-0342-x
|View full text |Cite
|
Sign up to set email alerts
|

A pathway approach to investigate the function and regulation of SREBPs

Abstract: The essential function of sterol regulatory element-binding proteins (SREBPs) in cellular lipid metabolism and homeostasis has been recognized for a long time, and the basic biological pathway involving SREBPs has been well described; however, a rapidly growing number of studies reveal the complex regulation of these SREBP transcription factors at multiple levels. This regulation allows the integration of signals of diverse pathways involving nutrients, contributing to cellular lipid and energy homeostasis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 106 publications
1
42
1
Order By: Relevance
“…Downregulation of SREBF-1 during early lactation was also observed by Graber et al (2010) and is reflected by a reduced expression of ACC and FASN in the peripartal period (Gross et al, 2013). Sterol regulatory element-binding factor 1, in contrast to SREBF-2, is known to be stimulated by insulin, as both SREBF-1 and insulin have been shown to induce lipogenesis (Daemen et al, 2013). Furthermore, insulin upregulates HMGCR in vitro (Bhasker and Friedmann, 2008) and, in diabetic rats, insulin was able to restore the decreased HMGCR levels (Ness et al, 1994).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Downregulation of SREBF-1 during early lactation was also observed by Graber et al (2010) and is reflected by a reduced expression of ACC and FASN in the peripartal period (Gross et al, 2013). Sterol regulatory element-binding factor 1, in contrast to SREBF-2, is known to be stimulated by insulin, as both SREBF-1 and insulin have been shown to induce lipogenesis (Daemen et al, 2013). Furthermore, insulin upregulates HMGCR in vitro (Bhasker and Friedmann, 2008) and, in diabetic rats, insulin was able to restore the decreased HMGCR levels (Ness et al, 1994).…”
Section: Discussionmentioning
confidence: 95%
“…Sterol regulatory element-binding factors are synthesized as endoplasmic reticulum membrane proteins. In the case of low cholesterol levels, they migrate to the Golgi apparatus where they are cleaved and then released as nuclear SREBF able to activate target genes (Desvergne et al, 2006;Daemen et al, 2013). During this translocation, posttranscriptional modifications of SREBF take place that might affect their further effects besides the mRNA expression level.…”
Section: Discussionmentioning
confidence: 99%
“…ACC and FAS, the key enzymes for the synthesis of fatty acids in the liver, are regulated by nuclear transcription factor SREBP-1c [15]. Studies have shown that the hepatic expression of SREBP-1c and its target lipid synthesis regulation genes, FAS and ACC, increase several times both in patients with NAFLD and in animal models such as transgenic mice, ob/ob mice (leptin deficiency results in an insulin resistance and hyperinsulinemia), and high-fat diet-fed mice and rats, which leads to deposition of a large amount of TG [1620].…”
Section: Discussionmentioning
confidence: 99%
“…Especially, SREBP2 is ubiquitouslly expressed, and relatively selective activator of cholesterol synthesis, as opposed to fatty acid synthesis, and regulates HMG-CoA reductase and low-density lipoprotein receptor (LDLR) genes 9, 10 . Since low levels of cholesterol stimulates SREBPs, the crucial role of SREBPs on liver steatosis and hyperlipedemia has been reported 9, 11 .…”
mentioning
confidence: 99%